The human and mouse GATA-6 genes utilize two promoters and two initiation codons. - Brewer, A; Gove, C; Davies, A; McNulty, C; Barrow, D; Koutsourakis, M; Farzaneh, F; Pizzey, J; Bomford, A; Patient, R (1999)
GATA-6 has been implicated in the regulation of myocardial differentiation during cardiogenesis. To determine how its expression is controlled, we have characterized the human and mouse genes. We have mapped their transcriptional start sites and demonstrate that two alternative promoters and 5' noncoding exons are utilized. Both transcript isoforms are expressed in the same tissue-specific and developmental stage-specific pattern, and their ratio appears similar wherever examined. The more upstream noncoding exon showed a substantial degree of homology between the two mammalian species, suggesting a conserved regulatory function. Moreover, in transfection assays we show that elements within this exon act to promote its transcription. Positive regulatory elements that effect transcription from the more downstream exon were not apparent in this assay, revealing a regulatory distinction between the two promoters. We also demonstrate alternative initiator codon usage in both the human and mouse GATA-6 genes. Both isoforms of the protein are synthesized in vitro regardless of which 5' noncoding exon is present in the RNA, although the larger protein has greater transcriptional activation potential in transfection assays. Thus, GATA-6 function in the cell is controlled by a complex interplay of transcriptional and translational regulation.